My family and other animals - Durrell, Gerald (London : Penguin books, 1977)
The book is a humorous memoir about Gerald Durrell$1 (Bs childhood when his family moved from England to the Greek island of Corfu in the 1930s. Gerald, a young boy fascinated by animals, spends his days exploring nature and collecting creatures, while his eccentric family members bring chaos and comedy to everyday life. Through funny and heartwarming stories, the book celebrates the joys of family, childhood curiosity, and the beauty of the natural world.s